Upaya Minimalisasi Komplikasi Persalinan dengan Asuhan Komplementer pada Kelompok Ibu Hamil Risiko Tinggi - Linda Yanti; Surtiningsih Surtiningsih (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
Introduction: In Karangmangu Village there are 37 pregnant women, from the results of the examination it is known that only 40.5% of pregnant women have a mild risk while 59.5% have a moderate to high risk such as maternal age <20 years or >35 years, anemia, lack of energy chronic kidney disease, vulvar varicose veins, hepatitis and 1 HIV positive pregnant woman. The purpose of this activity is the formation of a companion group for high-risk pregnant women, early detection and monitoring of high-risk pregnant women, preparation and planning for childbirth through physical and psychological preparation that is integrated with complementary care. Methods: preparation and coordination with village midwives and village officials, then screening and outreach to participants, namely all pregnant women and 37 pregnant women who were at high risk with early detection methods, lectures, discussions and deliberation Results: The formation of a companion group for high-risk IU. From the results of early detection, it was found that there were pregnant women with preeclampsia and old age, anemia, diabetes mellitus, chronic energy deficiency, urine protein, blood glucose. Detection of hypertension found that pregnant women are at risk of hypertension by examining the cold pressor test and increasing knowledge and skills. Conclusion: The formation of a companion group for high-risk pregnant women who can perform early detection and monitoring of high-risk pregnant women, preparation and planning for childbirth through physical and psychological preparation that is integrated with complementary care.